Professionalisierung in Lernberatungsgesprächen Theoretische Grundlegungen und empirische Untersuchungen - Wrana, Daniel; Maier Reinhard, Christiane (Beiträge der Schweizer Bildungsforschung, 2012)
In the process of professionalising teachers, not only knowledge and skills on a more fundamental level but also understanding and one's own positions on teaching and learning develop. Learning and professionalisation processes were examined in the empirical studies in this volume during the beginning of the studies to become a primary teacher within the framework of a self-learning architecture in which web-based learning activities are interwoven with individual subject-related learning counselling interviews. In the learning counselling interviews, individual discussions between lecturers and students about teaching and learning in the subject didactics of mathematics and music, art pedagogy and educational science can be observed. The studies on the development of professional convictions also look at the interactions in the pedagogical form of action of the learning counselling interview and proceed with the methodological approach of an analysis of discursive practices. Further studies examine transformations of the professional habitus, intervention practices in the conversations, the emotional dimension of learning and the temporal challenges in self-learning architectures.